DEVELOPING AUDIO-VISUAL MEDIA BY USING VIDEOPAD FOR TEACHING WRITING TO XI GRADE STUDENTS OF SMA N 11 MEDAN - Pelita Hutabarat; Isli Iriani Indiah Pane; Indra Hartoyo (TRANSFORM : Journal of English Language Teaching and Learning, 2019)
This was a conducted Research and development (R & D) study which concerned with the using of appropriate teaching and learning media. The objectives of this study were to find out the existing teaching media used in XI grade students of SMA N 11 Medan and to develop Audio-Visual media by using VideoPad for teaching writing Analytical Exposition Text. The data was gathered in the preliminary data by using interview and questionnaire on XI grade students and the English teacher. Then need analysis was done through questionnaire and interview as well. This research described the existing media available in the school and how it is used in English teaching and learning process that a development should be done. According to the result of the need analysis there were only 18% of the students considered that the teaching and learning process was helpful. It also showed information about students‟ choice of method and media to learning writing. By considering the result of the need analysis, an Audio-Visual media then developed as a teaching and learning aid of writing Analytical Exposition text. The product had later been assessed by two experts to find out the eligibility of the media. Through the experts‟ assessment which was contained of 4 scoring criterias, it was known that the eligibility of the media was “Very Good” based on the scoring criteria.  Keywords: Teaching and Learning Writing, Audio-Visual media, Analytical Exposition, VideoPad.